A checklist of fish fauna of Shuklaphanta National Park, Kanchanpur, Nepal - Poudyal, Laxman Prasad; Thapa, Ganesh Bahadur; Poudyal, Bishal (Journal of Natural History Museum, 2022)
An ichthyological survey along with a desk study was carried out at Shuklaphanta National Park, Kanchanpur, Nepal which harbours varieties of fish fauna. To this end, field surveys were held during the spring (March to April) and the autumn (September to October) in 2020 aiming to determine the fish checklist present in the study area. Cast net of different mesh sizes, scoop net, hook and line, flow modification, and local traps of bamboo baskets were the sampling gears employed to collect fish samples. Based on the present survey along with historical records, a combined fish checklist depicted a total of 88 fish species belonging to 7 orders, 21families and 49 genera which apart from 35 fish species adopted from the past studies carried out from 1973 to 2019, and 53 species were recorded during our field survey in 2020. This paper indicates the need for further exploration and studies and proper sustainable management for conserving important fish fauna from being overexploited.